Discord-Based COMPILE Application Model in Improving the Effectiveness of Teachers and Education Staff Management - Laurentia Prabaniardi Kartikasari; Ade Iriani; Sophia Tri Satyawati (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to develop a Discord-based COMPILE application model to improve the effectiveness of teachers and education staff management. This research is a Borg & Gall Research and Development (R&D) model with sequential explanatory mixed methods (qualitative and quantitative). Product development on the model uses the ADDIE development model, namely: Analysis, Design, Development, Implementation, and Evaluation. Developmental research was conducted at Tunas Bangsa Elementary School, Kuburaya, West Kalimantan. The research subjects were school directors, principals, teachers, and education staff. Research results were validated using technique triangulation and source triangulation methods. Qualitative data analysis used the Miles & Huberman model, while quantitative data analysis used the Likert scale. The results of the IT expert validation assessment showed a score percentage of 93%, the management expert validation result was 84%, and the results of the field trial with users (management, teachers, staff) showed a score of 82%. Thus, respectively showed the results of each validation and trial in a row as "Very Good", "Good" and "Good". So, the product, a Discord-based COMPILE application model, is feasible, acceptable, and can be used to improve the effectiveness of the school's management of teachers and education staff resources.